Sted, landskab, rum - Ringgaard, Dan (Slagmark - Tidsskrift for idéhistorie, 2018)
The article discusses matters concerning place by way of three prose poems by Danish writer Louis Jensen. The readings understand place by way of the neighbouring concepts of landscape and space. They set out from a phenomenological understanding of place, presenting basic insights of this approach (especially using the works of Edward S. Casey) and proceeds by way of the challenges given by the prose poems to a critique of phenomenological place theory. The critique points out that it tends to marginalize historic and semiotic aspects of place and questions its insistence on continuity between experience and knowledge. Instead the article suggests that a global sense of place involves discontinuity between place and space, and further more it is argued that the idea in Casey that place has been overruled by space in the modern era, might by correct from the point of view of philosophy, but it is not in accordance with the history of art and literature.